2011
DOI: 10.1002/jbm.a.33251
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of antimicrobial peptides using self‐organized TiO2 nanotube arrays for peri‐implant infections

Abstract: Peri-implant infections have been reported as one of the major complications that lead to the failure of orthopedic implants. An ideal solution to the peri-implant infection is to locally deliver antimicrobial agents through the implant surface. The rising problem of infections caused by multiple antibiotic-resistant bacteria makes traditional antibiotics less desirable for the prevention of peri-implant infections. One of the promising alternatives is the family of antimicrobial peptides (AMPs). In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 54 publications
3
85
0
Order By: Relevance
“…Subsequently, the cumulative drug release was close to the linear regression with the square root of time, suggesting a slow and stable release up to 7 days. The release profile was similar to those reported by Ma et al 32 and Lai et al, 33 who used anodized titanium as an HHC-36 or enrofloxacin hydrochloride carrier. The release profiles were similar for GL13K-TNTs and MNA-TNTs, but a slower release was achieved by GL13K-TNTs.…”
supporting
confidence: 86%
“…Subsequently, the cumulative drug release was close to the linear regression with the square root of time, suggesting a slow and stable release up to 7 days. The release profile was similar to those reported by Ma et al 32 and Lai et al, 33 who used anodized titanium as an HHC-36 or enrofloxacin hydrochloride carrier. The release profiles were similar for GL13K-TNTs and MNA-TNTs, but a slower release was achieved by GL13K-TNTs.…”
supporting
confidence: 86%
“…15 It has been widely shown that antibiotic-loaded TNTs are able to reduce bacterial adhesion, while retaining or improving normal osteoblast adhesion and differentiation. 13,[16][17][18][19] Various metal cations that possess antibacterial properties, such as Ag, Zn, and Cu, have been introduced into TNT arrays to enhance the antibacterial activity of TNT-based Ti implants. [20][21][22][23][24] Nevertheless, their potential toxicity and antibacterial durability have yet to be improved and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 Peptide binding to TiO 2 NTs has been used predominantly for studying the increase of cell adhesion and osteogenic gene expression 22,23,49 as well as for soft tissue interactions 24 and local delivery of antimicrobial peptides. 50 A hexapeptide motif was found to bind electrostatically to titanium surfaces, with potential important osteogenic consequences. 17 Therefore, we tested the binding of plasma proteins with different molecular weights, charges, and functions to TiO 2 NTs with specific diameters.…”
Section: Introductionmentioning
confidence: 99%
“…EG-based electrolytes, with hydrofluoric acid as the source of F -ions with specific amount of water, were used in the second anodization step, under various applied potentials for obtaining the desired different diameter NTs. Specifically, the electrolyte was EG plus 8 M water plus 0.2 M hydrofluoric acid and the anodization time of 2.5 hours was used for obtaining all nanostructures (15,50, and 100 nm), while the applied potential was 58 V for 100 nm, 20 V for 50 nm, and 10 V for 15 nm. The NTs thus formed were kept in ethanol for 2 hours to remove all organic components from the electrolyte, washed with distilled water, and dried under nitrogen stream.…”
mentioning
confidence: 99%